Silver paste, preparation method thereof and photovoltaic cell

By preparing and applying silver paste with high adhesion, the problem of poor working stability of heterojunction photovoltaic cells is solved, and the service life and reliability of photovoltaic cells are significantly improved.

CN119626628AInactive Publication Date: 2025-03-14XIAN RARE METAL MATERIALS RES INST CO LTD

Patent Information

Application Number
CN202510158208.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-13
Publication Date
2025-03-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing heterojunction photovoltaic cells have poor working stability, resulting in poor service life and reliability.

Method used

A silver paste is provided and a preparation method thereof. By adding composite resin, silver powder and cross-linked curing mixture to the solvent, and stirring and grinding, the viscosity and fineness of the silver paste are adjusted to improve its adhesion.

Benefits of technology

It significantly improves the surface adhesion of silver paste, reduces the probability of electrode falling off, and improves the working stability and service life of photovoltaic cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119626628A_ABST
    Figure CN119626628A_ABST
Patent Text Reader

Abstract

The invention relates to silver paste, a preparation method thereof and a photovoltaic cell. The silver paste can be used for the photovoltaic cell. The preparation method of the silver paste comprises the following steps: adding composite resin into a solvent to form an organic carrier; adding silver powder and a cross-linking curing mixing agent into the organic carrier, and stirring to obtain initial silver paste; adjusting the viscosity of the initial silver paste and / or the fineness of the initial silver paste to obtain silver paste; wherein the composite resin comprises hydroxyl modified polyester resin. The silver paste prepared through the preparation method of the silver paste has high adhesive force, the working stability of a photovoltaic cell can be improved, and the service life of the photovoltaic cell can be prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the technical field of photovoltaic cell manufacturing, and in particular to a silver paste and a preparation method thereof, and a photovoltaic cell. Background Art

[0002] In recent years, heterojunction photovoltaic cells have stood out among many photovoltaic cells due to their performance advantages such as high energy conversion efficiency, low process temperature and high bifaciality, and have become one of the most promising high-efficiency photovoltaic cells.

[0003] However, existing heterojunction photovoltaic cells have poor operating stability, resulting in poor service life and reliability.

[0004] It should be noted that the information disclosed in the above background technology section is only used to enhance the understanding of the background of the present disclosure, and therefore may include information that does not constitute the prior art known to ordinary technicians in the field. Summary of the invention

[0005] The present disclosure aims to provide a silver paste and a preparation method thereof, and a photovoltaic cell. The silver paste has high adhesion, can improve the working stability of the photovoltaic cell, and increase the service life of the photovoltaic cell.

[0006] In one aspect, the present disclosure provides a method for preparing silver paste, wherein the silver paste is used for photovoltaic cells, and the method for preparing the silver paste comprises: adding a composite resin into a solvent to form an organic vehicle; Adding silver powder and a cross-linking curing agent into the organic carrier and stirring the mixture to obtain an initial silver paste; Adjusting the viscosity of the initial silver paste and / or the fineness of the initial silver paste to obtain the silver paste; Wherein, the composite resin includes hydroxyl-modified polyester resin.

[0007] In an exemplary embodiment of the present disclosure, the composite resin further includes: one or more of epoxy resin, polyurethane resin, acrylic resin, chloroacetic resin, phenolic resin and silicone resin.

[0008] In an exemplary embodiment of the present disclosure, the cross-linking curing mixture comprises: a curing agent and an additive; Wherein, the additives include one or more of a coupling agent, a dispersant and a thixotropic agent.

[0009] In an exemplary embodiment of the present disclosure, the curing agent includes: a blocked isocyanate curing agent.

[0010] In an exemplary embodiment of the present disclosure, the deblocking temperature of the blocked isocyanate curing agent is less than or equal to 200°C.

[0011] In an exemplary embodiment of the present disclosure, the silver powder is a mixture of flaky silver powder and granular silver powder.

[0012] In an exemplary embodiment of the present disclosure, in the silver paste, the weight of the organic vehicle is 100 parts by weight, the weight of the silver powder is 500 parts by weight to 1000 parts by weight, and the weight of the cross-linking curing mixture is 25 parts by weight to 88 parts by weight.

[0013] In an exemplary embodiment of the present disclosure, adjusting the viscosity of the initial silver paste and / or the fineness of the initial silver paste to obtain the silver paste includes: Grinding the initial silver paste to adjust the viscosity of the initial silver paste to 80 Pa·s to 150 Pa·s, to obtain the silver paste; And / or, the initial silver paste is ground so that the fineness of the initial silver paste is less than 5 μm to obtain the silver paste.

[0014] Another aspect of the present disclosure provides a silver paste, which is prepared by any one of the above-mentioned methods for preparing the silver paste.

[0015] In another aspect, the present disclosure provides a photovoltaic cell, comprising: substrate; The electrode is formed on the surface of the substrate, and the electrode is made by the silver paste mentioned above.

[0016] The technical solution provided by the present disclosure can achieve the following beneficial effects: The present disclosure provides a method for preparing silver paste. In the method for preparing silver paste, a composite resin including a hydroxyl-modified polyester resin is added to a solvent, thereby ensuring that the prepared silver paste contains a large number of unsaturated functional groups, thereby enhancing the interaction between the prepared silver paste and the substrate molecules of the photovoltaic cell, thereby significantly improving the surface adhesion of the silver paste.

[0017] Therefore, when the electrodes in photovoltaic cells are made of this silver paste, the probability of electrode falling off can be reduced, thereby improving the working stability of the electrodes, and then improving the working stability of the photovoltaic cells, effectively and significantly improving the service life and reliability of the photovoltaic cells.

[0018] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present disclosure. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] The accompanying drawings herein are incorporated into the specification and constitute a part of the specification, illustrate embodiments consistent with the present disclosure, and together with the specification are used to explain the principles of the present disclosure. Obviously, the accompanying drawings described below are only some embodiments of the present disclosure, and for ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without creative work.

[0020] Figure 1 A schematic flow chart of a method for preparing silver paste according to an exemplary embodiment of the present disclosure is shown.

[0021] Figure 2 A schematic flow chart of a method for preparing silver paste according to another exemplary embodiment of the present disclosure is shown. DETAILED DESCRIPTION

[0022] Example embodiments will now be described more fully with reference to the accompanying drawings. However, example embodiments can be implemented in a variety of forms and should not be construed as limited to the embodiments set forth herein; rather, these embodiments are provided so that this disclosure will be comprehensive and complete and will fully convey the concepts of the example embodiments to those skilled in the art. The same reference numerals in the figures represent the same or similar structures, and thus their detailed description will be omitted.

[0023] Although relative terms such as "upper" and "lower" are used in this specification to describe the relative relationship of one component of the illustration to another component, these terms are used in this specification only for convenience, such as according to the orientation of the examples described in the drawings. It is understood that if the device of the illustration is turned upside down, the component described as "upper" will become the component "lower". When a structure is "on" other structures, it may mean that the structure is formed integrally on the other structure, or that the structure is "directly" disposed on the other structure, or that the structure is "indirectly" disposed on the other structure through another structure.

[0024] The terms "a", "an", "the", and "said" are used to indicate the presence of one or more elements / components / etc.; the terms "including" and "having" are used to express an open-ended inclusion and mean that additional elements / components / etc. may exist in addition to the listed elements / components / etc.; the terms "first" and "second", etc. are used merely as labels and are not intended to limit the quantity of their objects.

[0025] The present disclosure provides a photovoltaic cell, which may be a heterojunction photovoltaic cell, but is not limited thereto. The photovoltaic cell may include: a substrate, the substrate may include a PN junction structure, and when the photovoltaic cell is a heterojunction photovoltaic cell, the substrate may include a heterogeneous PN junction structure.

[0026] The photovoltaic cell may further include: an electrode, which may be formed on the surface of the substrate. The electrode may include: a first electrode and a second electrode, which may be formed on both sides of the substrate, namely: the first electrode may be formed on the side of the substrate close to the P-type silicon substrate, and the second electrode may be formed on the side of the substrate close to the N-type silicon substrate; or, the first electrode may be formed on the side of the substrate close to the N-type silicon substrate, and the second electrode may be formed on the side of the substrate close to the P-type silicon substrate.

[0027] In some embodiments, the electrode can be made of silver paste. Specifically, the electrode can be made by screen printing silver paste process and sintering process. Therefore, the performance of the silver paste directly determines the performance of the electrode provided by the present disclosure, and also determines the performance of the photovoltaic cell including the electrode.

[0028] Therefore, some embodiments of the present disclosure provide a method for preparing silver paste, which is used to prepare the silver paste for making the above-mentioned electrode. Figure 1 As shown, the preparation method of silver paste may include: Step S10: adding a composite resin into a solvent to form an organic vehicle.

[0029] Step S20: adding silver powder and a cross-linking curing agent into an organic carrier and stirring the mixture to obtain an initial silver paste.

[0030] Step S30, adjusting the viscosity of the initial silver paste and / or the fineness of the initial silver paste to obtain the silver paste.

[0031] In some embodiments, the solvent may include one or more of diethylene glycol butyl ether, diethylene glycol butyl ether acetate, methyl acetate, ethyl acetate, propylene glycol, propylene glycol methyl ether acetate, cyclohexanone, isophorone, dimethyl sulfoxide, and the like.

[0032] In some embodiments, the composite resin may include a hydroxyl-modified polyester resin, thereby ensuring that the prepared silver paste contains a large number of unsaturated functional groups, thereby enhancing the interaction between the prepared silver paste and the substrate molecules of the photovoltaic cell, thereby significantly improving the surface adhesion of the silver paste.

[0033] Therefore, when the electrodes in photovoltaic cells are made of this silver paste, the probability of electrode falling off can be reduced, thereby improving the working stability of the electrodes, and then improving the working stability of the photovoltaic cells, effectively and significantly improving the service life and reliability of the photovoltaic cells.

[0034] In some embodiments, the hydroxyl value of the hydroxyl-modified polyester resin may be greater than or equal to 100 mgKOH / g, and may be less than or equal to 300 mgKOH / g. For example, the hydroxyl value of the hydroxyl-modified polyester resin may be 100 mgKOH / g, 120 mgKOH / g, 140 mgKOH / g, 160 mgKOH / g, 180 mgKOH / g, 200 mgKOH / g, 220 mgKOH / g, 240 mgKOH / g, 260 mgKOH / g, 280 mgKOH / g, 300 mgKOH / g, etc.

[0035] In some embodiments, the composite resin may also include one or more of epoxy resin, polyurethane resin, acrylic resin, chloroacetic resin, phenolic resin and silicone resin. The resins used in this embodiment are all multifunctional resins, so by mixing these multifunctional resins with hydroxyl-modified polyester resins to form composite resins, the number of unsaturated functional groups in the prepared silver paste can be further increased, and the interaction force between the prepared silver paste and the substrate molecules of the photovoltaic cell can be further increased, so that the surface adhesion of the silver paste can be further improved. Such an arrangement can further improve the stability of the electrode operation, thereby further improving the stability of the photovoltaic cell operation, and further improving the service life and reliability of the photovoltaic cell.

[0036] The cross-linking curing mixture may include: a curing agent. The curing agent may be a blocked isocyanate curing agent, so that the blocked isocyanate curing agent can release a large amount of isocyanate groups when the unblocking temperature is reached. The isocyanate groups have high reactivity, so that they can undergo cross-linking curing reactions with various functional groups such as hydroxyl, amino and carboxyl groups in the composite resin, thereby further improving the adhesion of the prepared silver paste.

[0037] Moreover, after the cross-linking and curing reaction between the isocyanate group and the composite resin, they can quickly cross-link to form a three-dimensional network structure, causing the volume of the entire silver paste system to shrink significantly. The composite resin has a large volume shrinkage rate, which can further shorten the distance between the silver powders, improve the conductivity of the prepared silver paste, and thus improve the performance of the photovoltaic cell.

[0038] At the same time, the silver paste prepared with the blocked isocyanate curing agent can also have good storage stability, which is beneficial to the preservation and transportation of the silver paste.

[0039] The unblocking temperature of the blocked isocyanate curing agent can be less than or equal to 200°C, for example: 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, etc. In this way, the curing temperature of the electrode made by the silver paste can be reduced to below 200°C, effectively reducing the thermal damage to the photovoltaic cell substrate caused by high temperature, and improving the product yield of the photovoltaic cell. In addition, in this way, the adhesion of the silver paste can be further improved.

[0040] Preferably, the unsealing temperature of the blocked isocyanate curing agent may be greater than or equal to 100°C and less than or equal to 150°C, for example: 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, etc. Such a setting can avoid the uncontrollable unsealing process of the blocked isocyanate curing agent due to the unsealing temperature being too low. At the same time, such a setting can also further reduce the unsealing temperature of the blocked isocyanate curing agent, further reduce the thermal damage to the photovoltaic cell substrate, and thus further improve the product yield of the photovoltaic cell.

[0041] In this embodiment, the blocked isocyanate curing agent can be selected from the blocked isocyanate curing agent model Basonat HI 100 produced by BASF AG, the blocked isocyanate curing agent model Basonat HI190B / S produced by BASF AG, the blocked isocyanate curing agent model Desmodur BL 3370 produced by Covestro AG, the blocked isocyanate curing agent model Desmodur N3300 produced by Covestro AG, the blocked isocyanate curing agent model XB-G282 produced by Mitsui Chemicals, the blocked isocyanate curing agent model B-897N produced by Mitsui Chemicals, etc.

[0042] In some embodiments, the cross-linking curing mixture may further include additives. The additives may include one or more of a coupling agent, a dispersant, and a thixotropic agent.

[0043] Among them, the coupling agent can be an organic silicon coupling agent, which can include: one or more of a coupling agent with model Z-6040, a coupling agent with model Z-6011, a coupling agent with model KBM-403, a coupling agent with model KH-550, a coupling agent with model KH-560, a coupling agent with model KH-570, etc.

[0044] The dispersant may include: polyvinyl pyrrolidone, oleic acid, oleylamine, castor oil, triolein, a dispersant with model number Dipersant-9327, a dispersant with model number DVK-9900, a dispersant with model number BYK-111, a dispersant with model number Span-85, or one or more thereof.

[0045] The thixotropic agent may be one or more of fumed silica, organic bentonite, hydrogenated castor oil, polyamide wax, a thixotropic agent with a model number of BYK-405, a thixotropic agent with a model number of BYK-410, and the like.

[0046] In some embodiments, the silver powder may be a mixture of flaky silver powder and granular silver powder. In this way, the flaky silver powder can be used to provide a good conductive path foundation and physical support for the prepared silver paste, and the granular silver powder can be used to fill the microscopic gaps in the prepared silver paste to enhance the compactness of the prepared silver paste, thereby improving the conductivity of the prepared silver paste, and further improving the performance of the photovoltaic cell.

[0047] In this embodiment, the particle size of the flaky silver powder can be 1 μm to 10 μm, for example, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, etc. This arrangement can ensure that the flaky silver powder has good physical support and conductive properties.

[0048] The particle size of the granular silver powder can be 10 μm to 100 μm, for example, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, etc. Such a configuration can be more conducive to the microscopic control of the granular silver powder filling the silver paste, and further improve the density of the prepared silver paste.

[0049] In some embodiments, in the silver paste, the weight of the organic vehicle is 100 parts by weight, the weight of the silver powder can be 500 to 1000 parts by weight, and the weight of the cross-linking curing agent can be 25 to 88 parts by weight. In the organic vehicle, the weight of the solvent can be 100 parts by weight, and the weight of the composite resin can be 20 to 200 parts by weight. In the cross-linking curing agent, the weight of the curing agent can be 10 to 50 parts by weight, and the weight of the additive can be 15 to 38 parts by weight. In the additive, the weight of the coupling agent can be 10 to 20 parts by weight, the weight of the dispersant can be 3 to 10 parts by weight, and the weight of the thixotropic agent can be 2 to 8 parts by weight.

[0050] That is, it can be understood that in the silver paste, the weight percentage of the organic carrier can be 8.4% to 16%, for example: 8.4%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, etc. The weight percentage of the silver powder can be 72.6% to 88%, for example: 72.6%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, etc. The weight percentage of the cross-linking curing agent can be 2.2% to 12.8%, for example: 2.2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 12.8%, etc. In the cross-linking and curing mixture, the weight percentage of the curing agent in the silver paste can be 0.8% to 7.5%, for example: 0.8%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 7.5%, etc., and the weight percentage of the additive in the silver paste can be 1% to 6%, for example: 1%, 2%, 3%, 4%, 5%, 6%, etc.

[0051] For example, in step S10, 20 to 200 parts by weight of a composite resin may be added to 100 parts by weight of a solvent to form an organic vehicle. In step S20, 500 to 1000 parts by weight of silver powder, 10 to 50 parts by weight of a curing agent, 10 to 20 parts by weight of a coupling agent, 3 to 10 parts by weight of a dispersant, and 2 to 8 parts by weight of a thixotropic agent may be added to 100 parts by weight of an organic vehicle and stirred to obtain an initial silver paste.

[0052] In step S10, the solvent and the composite resin may be stirred in a water bath at 60° C. to 80° C. to form an organic vehicle. In this way, the solvent and the composite resin may be heated evenly, thereby improving the mixing uniformity of the organic vehicle.

[0053] In step S20, the mixture of silver powder, cross-linking curing agent and organic carrier can be added to a mixer for stirring to obtain an initial silver paste, for example, a planetary mixer can be used, but is not limited thereto. The stirring time can be 60 minutes to 120 minutes, so as to ensure the uniformity of stirring and improve the performance of the prepared silver paste.

[0054] In some embodiments, in step S30, the initial silver paste may be ground to adjust the viscosity of the initial silver paste to 80 Pa·s to 150 Pa·s, for example, 80 Pa·s, 90 Pa·s, 100 Pa·s, 110 Pa·s, 120 Pa·s, 130 Pa·s, 140 Pa·s, 150 Pa·s, etc., to obtain silver paste. The silver paste may meet the requirements of screen printing.

[0055] Alternatively, the initial silver paste may be ground to a fineness of less than 5 μm, such as 0.1 μm, 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 4.5 μm, 4.9 μm, etc., to obtain a silver paste that can meet the requirements of screen printing.

[0056] Alternatively, the initial silver paste may be ground to adjust the viscosity of the initial silver paste to 80 Pa·s to 150 Pa·s, such as 80 Pa·s, 90 Pa·s, 100 Pa·s, 110 Pa·s, 120 Pa·s, 130 Pa·s, 140 Pa·s, 150 Pa·s, etc., and the fineness of the initial silver paste may be less than 5 μm, such as 0.1 μm, 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 4.5 μm, 4.9 μm, etc., to obtain the silver paste. The silver paste may further meet the requirements of screen printing.

[0057] In this embodiment, the initial silver paste can be added to a grinder for grinding to adjust the viscosity of the initial silver paste and / or the fineness of the initial silver paste. For example, the initial silver paste can be added to a three-roll grinder and ground for 3 to 5 times. However, this is not limited to this. The present disclosure does not limit the type of grinder and the number of grindings, and can be selected and set according to actual needs, which is within the protection scope of the present disclosure.

[0058] In some embodiments of the present disclosure, Figure 2 As shown, the preparation method of the silver paste may further include: Step S40, screen-printing the silver paste on the substrate surface of the photovoltaic cell, drying the silver paste, and measuring the square resistance and adhesion of the cured silver paste.

[0059] For example, the square resistance of the silver paste after curing at 150°C for 30 minutes can be measured by a four-probe square resistance tester, and the adhesion of the cured silver paste to the substrate can be tested by the 100-grid method. However, this embodiment does not limit the drying temperature and drying time of the silver paste, and can be selected and set according to actual needs.

[0060] The preparation method of the silver paste is further explained below through a plurality of specific examples and a comparative example.

[0061] Embodiment 1 In step S10, 10 parts by weight of a hydroxyl-modified polyester resin having a hydroxyl value of 200 mgKOH / g and 10 parts by weight of a polyurethane resin can be added to 100 parts by weight of diethylene glycol butyl ether acetate solvent, and the solvent and the composite resin can be stirred in a water bath at 80° C. to form an organic carrier.

[0062] In step S20, 800 parts by weight of flaky silver powder and 200 parts by weight of granular silver powder may be added to the above 100 parts by weight of the organic vehicle. The particle size of the flaky silver powder is 8 μm, and the particle size of the granular silver powder is 30 μm. 10 parts by weight of a coupling agent of model KH560, 5 parts by weight of a dispersant of model Dipersant-9327, 5 parts by weight of a polyamide wax thixotropic agent, and 20 parts by weight of a blocked isocyanate curing agent of model Desmodur BL 3370 may be added, and mixed and stirred for 60 minutes using a planetary mixer to form an initial silver paste.

[0063] In step S30, the initial silver paste may be added to a three-roll mill and ground three times to adjust the viscosity of the initial silver paste to 100 Pa·s and to make the fineness of the initial silver paste less than 5 μm to obtain the silver paste.

[0064] In step S40, the silver paste prepared in step S30 can be screen-printed on the substrate surface of the photovoltaic cell, and the silver paste can be dried at 150°C for 30 minutes. The square resistance of the silver paste after curing can be measured using a four-probe square resistance tester, and the adhesion of the cured silver paste to the substrate can be tested using the hundred-grid method.

[0065] Embodiment 2 In step S10, 10 parts by weight of a hydroxyl-modified polyester resin having a hydroxyl value of 200 mgKOH / g and 10 parts by weight of an epoxy resin of model E-51 can be added to 100 parts by weight of diethylene glycol butyl ether solvent, and the solvent and the composite resin can be stirred in a water bath at 80° C. to form an organic carrier.

[0066] In step S20, 800 parts by weight of flaky silver powder and 200 parts by weight of granular silver powder may be added to the above 100 parts by weight of the organic vehicle. The particle size of the flaky silver powder is 8 μm, and the particle size of the granular silver powder is 30 μm. 10 parts by weight of a coupling agent of model KH560, 5 parts by weight of a dispersant of model Dipersant-9327, 5 parts by weight of a polyamide wax thixotropic agent, and 20 parts by weight of a blocked isocyanate curing agent of model Desmodur BL 3370 may be added, and mixed and stirred for 60 minutes using a planetary mixer to form an initial silver paste.

[0067] In step S30, the initial silver paste may be added to a three-roll mill and ground three times to adjust the viscosity of the initial silver paste to 100 Pa·s and to make the fineness of the initial silver paste less than 5 μm to obtain the silver paste.

[0068] In step S40, the silver paste prepared in step S30 can be screen-printed on the substrate surface of the photovoltaic cell, and the silver paste can be dried at 150°C for 30 minutes. The square resistance of the silver paste after curing can be measured using a four-probe square resistance tester, and the adhesion of the cured silver paste to the substrate can be tested using the hundred-grid method.

[0069] Embodiment 3 In step S10, 10 parts by weight of a hydroxyl-modified polyester resin having a hydroxyl value of 200 mgKOH / g and 10 parts by weight of an acrylic resin may be added to 100 parts by weight of a propylene glycol solvent, and the solvent and the composite resin may be stirred in a water bath at 80° C. to form an organic vehicle.

[0070] In step S20, 800 parts by weight of flaky silver powder and 200 parts by weight of granular silver powder may be added to the above 100 parts by weight of the organic vehicle. The particle size of the flaky silver powder is 8 μm, and the particle size of the granular silver powder is 30 μm. 10 parts by weight of a coupling agent of model KH560, 5 parts by weight of a dispersant of model Dipersant-9327, 5 parts by weight of a polyamide wax thixotropic agent, and 20 parts by weight of a blocked isocyanate curing agent of model Desmodur BL 3370 may be added, and mixed and stirred for 60 minutes using a planetary mixer to form an initial silver paste.

[0071] In step S30, the initial silver paste may be added to a three-roll mill and ground three times to adjust the viscosity of the initial silver paste to 100 Pa·s and to make the fineness of the initial silver paste less than 5 μm to obtain the silver paste.

[0072] In step S40, the silver paste prepared in step S30 can be screen-printed on the substrate surface of the photovoltaic cell, and the silver paste can be dried at 150°C for 30 minutes. The square resistance of the silver paste after curing can be measured using a four-probe square resistance tester, and the adhesion of the cured silver paste to the substrate can be tested using the hundred-grid method.

[0073] Embodiment 4 In step S10, 10 parts by weight of a hydroxyl-modified polyester resin having a hydroxyl value of 200 mgKOH / g and 10 parts by weight of an acrylic resin can be added to 100 parts by weight of diethylene glycol butyl ether acetate solvent, and the solvent and the composite resin can be stirred in a water bath at 80° C. to form an organic carrier.

[0074] In step S20, 400 parts by weight of flaky silver powder and 100 parts by weight of granular silver powder may be added to the above 100 parts by weight of the organic vehicle. The particle size of the flaky silver powder is 8 μm, and the particle size of the granular silver powder is 30 μm. 10 parts by weight of a coupling agent of model KH560, 3 parts by weight of a dispersant of model Dipersant-9327, 2 parts by weight of a polyamide wax thixotropic agent, and 10 parts by weight of a blocked isocyanate curing agent of model Desmodur BL 3370 may be added, and mixed and stirred for 60 minutes using a planetary mixer to form an initial silver paste.

[0075] In step S30, the initial silver paste may be added to a three-roll mill and ground for three times to adjust the viscosity of the initial silver paste to 80 Pa·s and to make the fineness of the initial silver paste less than 5 μm to obtain the silver paste.

[0076] In step S40, the silver paste prepared in step S30 can be screen-printed on the substrate surface of the photovoltaic cell, and the silver paste can be dried at 150°C for 30 minutes. The square resistance of the silver paste after curing can be measured using a four-probe square resistance tester, and the adhesion of the cured silver paste to the substrate can be tested using the hundred-grid method.

[0077] Embodiment 5 In step S10, 10 parts by weight of a hydroxyl-modified polyester resin having a hydroxyl value of 200 mgKOH / g and 10 parts by weight of an acrylic resin can be added to 100 parts by weight of diethylene glycol butyl ether acetate solvent, and the solvent and the composite resin can be stirred in a water bath at 80° C. to form an organic carrier.

[0078] In step S20, 400 parts by weight of flaky silver powder and 100 parts by weight of granular silver powder may be added to the above 100 parts by weight of the organic vehicle. The particle size of the flaky silver powder is 8 μm, and the particle size of the granular silver powder is 30 μm. 20 parts by weight of a coupling agent of model KH560, 10 parts by weight of a dispersant of model Dipersant-9327, 8 parts by weight of a polyamide wax thixotropic agent, and 50 parts by weight of a blocked isocyanate curing agent of model Desmodur BL 3370 may be added, and mixed and stirred for 60 minutes using a planetary mixer to form an initial silver paste.

[0079] In step S30, the initial silver paste may be added to a three-roll mill and ground three times to adjust the viscosity of the initial silver paste to 150 Pa·s and to make the fineness of the initial silver paste less than 5 μm to obtain the silver paste.

[0080] In step S40, the silver paste prepared in step S30 can be screen-printed on the substrate surface of the photovoltaic cell, and the silver paste can be dried at 150°C for 30 minutes. The square resistance of the silver paste after curing can be measured using a four-probe square resistance tester, and the adhesion of the cured silver paste to the substrate can be tested using the hundred-grid method.

[0081] Embodiment 6 In step S10, 10 parts by weight of a hydroxyl-modified polyester resin having a hydroxyl value of 200 mgKOH / g and 10 parts by weight of an acrylic resin can be added to 100 parts by weight of diethylene glycol butyl ether acetate solvent, and the solvent and the composite resin can be stirred in a water bath at 80° C. to form an organic carrier.

[0082] In step S20, 800 parts by weight of flaky silver powder and 200 parts by weight of granular silver powder may be added to the above 100 parts by weight of the organic vehicle. The particle size of the flaky silver powder is 8 μm, and the particle size of the granular silver powder is 30 μm. 10 parts by weight of a coupling agent of model KH560, 3 parts by weight of a dispersant of model Dipersant-9327, 2 parts by weight of a polyamide wax thixotropic agent, and 10 parts by weight of a blocked isocyanate curing agent of model Desmodur BL 3370 may be added, and mixed and stirred for 60 minutes using a planetary mixer to form an initial silver paste.

[0083] In step S30, the initial silver paste may be added to a three-roll mill and ground for three times to adjust the viscosity of the initial silver paste to 80 Pa·s and to make the fineness of the initial silver paste less than 5 μm to obtain the silver paste.

[0084] In step S40, the silver paste prepared in step S30 can be screen-printed on the substrate surface of the photovoltaic cell, and the silver paste can be dried at 150°C for 30 minutes. The square resistance of the silver paste after curing can be measured using a four-probe square resistance tester, and the adhesion of the cured silver paste to the substrate can be tested using the hundred-grid method.

[0085] Embodiment 7 In step S10, 10 parts by weight of a hydroxyl-modified polyester resin having a hydroxyl value of 200 mgKOH / g and 10 parts by weight of an acrylic resin can be added to 100 parts by weight of diethylene glycol butyl ether acetate solvent, and the solvent and the composite resin can be stirred in a water bath at 80° C. to form an organic carrier.

[0086] In step S20, 800 parts by weight of flaky silver powder and 200 parts by weight of granular silver powder may be added to the above 100 parts by weight of the organic vehicle. The particle size of the flaky silver powder is 8 μm, and the particle size of the granular silver powder is 30 μm. 20 parts by weight of a coupling agent of model KH560, 10 parts by weight of a dispersant of model Dipersant-9327, 8 parts by weight of a polyamide wax thixotropic agent, and 50 parts by weight of a blocked isocyanate curing agent of model Desmodur BL 3370 may be added, and mixed and stirred for 60 minutes using a planetary mixer to form an initial silver paste.

[0087] In step S30, the initial silver paste may be added to a three-roll mill and ground for three times to adjust the viscosity of the initial silver paste to 80 Pa·s and to make the fineness of the initial silver paste less than 5 μm to obtain the silver paste.

[0088] In step S40, the silver paste prepared in step S30 can be screen-printed on the substrate surface of the photovoltaic cell, and the silver paste can be dried at 150°C for 30 minutes. The square resistance of the silver paste after curing can be measured using a four-probe square resistance tester, and the adhesion of the cured silver paste to the substrate can be tested using the hundred-grid method.

[0089] Comparative Example In step S10, 10 parts by weight of chloroacetate resin and 10 parts by weight of polyurethane resin may be added to 100 parts by weight of diethylene glycol butyl ether acetate solvent, and the solvent and the composite resin may be stirred in a water bath at 80° C. to form an organic vehicle.

[0090] In step S20, 800 parts by weight of flaky silver powder and 200 parts by weight of granular silver powder may be added to the above 100 parts by weight of the organic vehicle. The particle size of the flaky silver powder is 8 μm, and the particle size of the granular silver powder is 30 μm. 10 parts by weight of a coupling agent of model KH560, 5 parts by weight of a dispersant of model Dipersant-9327, 5 parts by weight of a polyamide wax thixotropic agent, and 20 parts by weight of a blocked isocyanate curing agent of model Desmodur BL 3370 may be added, and mixed and stirred for 60 minutes using a planetary mixer to form an initial silver paste.

[0091] In step S30, the initial silver paste may be added to a three-roll mill and ground three times to adjust the viscosity of the initial silver paste to 100 Pa·s and to make the fineness of the initial silver paste less than 5 μm to obtain the silver paste.

[0092] In step S40, the silver paste prepared in step S30 can be screen-printed on the substrate surface of the photovoltaic cell, and the silver paste can be dried at 150°C for 30 minutes. The square resistance of the silver paste after curing can be measured using a four-probe square resistance tester, and the adhesion of the cured silver paste to the substrate can be tested using the hundred-grid method.

[0093] The above-mentioned examples 1, 2, 3, 4, 5, 6 and 7 are all specific examples of the method for preparing the silver paste provided by the present disclosure, and the control examples are not prepared by the method for preparing the silver paste provided by the present disclosure. Specifically, the composite resin in the control examples does not use a hydroxyl-modified polyester resin.

[0094] Table 1 Comparison table of seven specific embodiments and comparative embodiments

[0095] It should be noted that 3B is one of the grades in the grade standard for material surface adhesion. In this grade standard, 0B is the lowest grade, and the material surface adhesion it represents is the lowest. In this grade standard, 5B is the highest grade, and the material surface adhesion it represents is the highest. Among them, the adhesion of materials of grade 1B is greater than the adhesion of materials of grade 0B, the adhesion of materials of grade 2B is greater than the adhesion of materials of grade 1B, the adhesion of materials of grade 3B is greater than the adhesion of materials of grade 2B, the adhesion of materials of grade 4B is greater than the adhesion of materials of grade 3B, and the adhesion of materials of grade 5B is greater than the adhesion of materials of grade 4B.

[0096] It can be seen from Table 1 above that the adhesion of the silver pastes prepared in Example 1, Example 2, Example 3, Example 4, Example 5, Example 6 and Example 7 is greater than or equal to 3B, while the adhesion of the silver paste prepared in the control example is only 2B. It can be seen that the silver paste prepared by the preparation method of the silver paste provided by the present disclosure has a high adhesion, which can reduce the probability of the electrode made using the silver paste falling off, thereby improving the stability of the electrode operation, and then improving the stability of the photovoltaic cell operation, effectively and significantly improving the service life and reliability of the photovoltaic cell.

[0097] At the same time, the square resistance of the silver paste prepared in Example 1, Example 2, Example 4, Example 5 and Example 6 is greater than the square resistance of the silver paste prepared in the control example. It can be seen that the silver paste prepared by the preparation method of the silver paste provided by the present disclosure has a higher electrical conductivity, which can improve the electrical conductivity of the electrode made by the silver paste, and can improve the performance of the photovoltaic cell.

[0098] Those skilled in the art will readily appreciate other embodiments of the present disclosure after considering the specification and practicing the invention disclosed herein. The present disclosure is intended to cover any variations, uses or adaptations of the present disclosure, which follow the general principles of the present disclosure and include common knowledge or customary techniques in the art that are not disclosed in the present disclosure. The description and examples are intended to be exemplary only, and the true scope and spirit of the present disclosure are indicated by the appended claims.

Claims

1. A method for preparing silver paste, characterized in that: The silver paste is used for photovoltaic cells, and the preparation method of the silver paste comprises: adding a composite resin into a solvent to form an organic vehicle; Adding silver powder and a cross-linking curing agent into the organic carrier and stirring the mixture to obtain an initial silver paste; Adjusting the viscosity of the initial silver paste and / or the fineness of the initial silver paste to obtain the silver paste; Wherein, the composite resin includes hydroxyl-modified polyester resin.

2. The method for preparing silver paste according to claim 1, characterized in that: The composite resin also includes one or more of epoxy resin, polyurethane resin, acrylic resin, chloroacetic resin, phenolic resin and silicone resin.

3. The method for preparing silver paste according to claim 1, characterized in that: The cross-linking curing mixture comprises: a curing agent and an additive; Wherein, the additives include one or more of a coupling agent, a dispersant and a thixotropic agent.

4. The method for preparing silver paste according to claim 3, characterized in that: The curing agent includes: a blocked isocyanate curing agent.

5. The method for preparing silver paste according to claim 4, characterized in that: The deblocking temperature of the blocked isocyanate curing agent is less than or equal to 200°C.

6. The method for preparing silver paste according to any one of claims 1 to 5, characterized in that: The silver powder is a mixture of flaky silver powder and granular silver powder.

7. The method for preparing silver paste according to any one of claims 1 to 5, characterized in that: In the silver paste, the weight of the organic vehicle is 100 parts by weight, the weight of the silver powder is 500 parts by weight to 1000 parts by weight, and the weight of the cross-linking curing mixture is 25 parts by weight to 88 parts by weight.

8. The method for preparing silver paste according to any one of claims 1 to 5, characterized in that: The step of adjusting the viscosity of the initial silver paste and / or the fineness of the initial silver paste to obtain the silver paste comprises: Grinding the initial silver paste to adjust the viscosity of the initial silver paste to 80 Pa·s to 150 Pa·s, to obtain the silver paste; And / or, the initial silver paste is ground so that the fineness of the initial silver paste is less than 5 μm to obtain the silver paste.

9. A silver paste, characterized in that: The silver paste is prepared by the silver paste preparation method described in any one of claims 1 to 8.

10. A photovoltaic cell, characterized in that: include: substrate; An electrode is formed on the surface of the substrate, and the electrode is made of the silver paste described in claim 9.

Citation Information

Patent Citations

  • 3D (three-dimensional) flash metal powder coating and preparation method thereof

    CN109486399A

  • Low-temperature conductive silver paste suitable for fine grid overprinting and used for photovoltaic HJT battery and preparation method of low-temperature conductive silver paste

    CN115831439A

  • TOPCon back silver paste prepared from cross-linked carrier and preparation method of TOPCon back silver paste

    CN117012432A

  • Conductive silver paste and preparation method thereof

    CN118737522A

  • Back fine grid silver paste for TOPCon solar cell and preparation method of back fine grid silver paste

    CN118969356A

Cited By

  • Silver paste for photovoltaic cell and preparation method of silver paste for photovoltaic cell

    CN121790055A

  • Silver paste for photovoltaic cell and method for preparing silver paste for photovoltaic cell

    CN121790055B